Response of different levels of ash and saw dust applications on Bambara Groundnut performance in Ifite-Ogwari, Derived Savannah Zone of Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
In this study, the response of Bambara groundnut (BGN) in terms of growth and yield to different levels of sawdust was evaluated, a randomized complete block design (RCBD)  fitted in to a 2× 4 factorial experiment was conducted at the Training and Research farm of Nnamdi Azikiwe University, Ifite-Ogwari.  Two (2)  types of soil amendments (sawdust and ash) at four (4) levels of applications including standard (Control, 10 tons/ha, 20 tons/ha, and 30 tons/ha), each replicated three times. Result indicated that, ash treated plots had a greater number of stems, leaf, canopy and biomass while sawdust treated plots had taller plants at 2 weeks after planting (WAP) (9.28cm) and 4WAP (17.44cm) probably due to its excellent mulching effects. Virtually on all the treatments growth and yield parameters, 10kg and 20kg rates the soil amendments were not significantly different except for pod weights. Ash at 20kg rate produced (640kg/ha) which was not significantly different from sawdust(706kg/ha) at the same rate. It is recommend the use of sawdust ash since most sawdust have high carbon / Nitrogen ratio so they tend to mop up soluble soil nutrients which might adversely affect the soil on long run. Although sawdust contain plant nutrients, they are not readily available to the plants until after their decomposition. Therefore, for economic and environmental reasons we recommend the use of 10tons of sawdust ash for the cultivation of Bambara nut in the Research area if available.
Keywords: Ash; Bambara groundnut; Mulching; Sawdust; Soil amendments